2018
DOI: 10.15421/021874
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the spectrum of proteins and phospholipids in tissues of rats exposed to thiosulfonates

Abstract: Esters of thiosulfoacids demonstrate a wide range of biological activity. One of their effects is the influence on the metabolism of proteins and lipids in the body. Therefore, the purpose of our experiment was to study the impact of synthesized thiosulfonates on the total content of proteins and phospholipids, as well as their spectrum in the blood, liver, and kidney of rats. For the experiment, allyl, ethyl, and methyl esters of thiosulfoacid were used. The protein profile of rat tissues was investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…Previous studies have shown that ethylthiosulfanylate is involved in regulation of the activity of the lipid metabolism enzymes and performs the redistribution of lipid classes and a decrease in mono-, di-, triglycerides and free fatty acids in the rat liver [8]. Administration of ethylthio sulfanylate induces the increase of total protein and albumin content in rat blood plasma [12]. Also, ethylthiosulfanylate is an effective agent against fungal infections and has antimicrobial effect [9].…”
mentioning
confidence: 99%
“…Previous studies have shown that ethylthiosulfanylate is involved in regulation of the activity of the lipid metabolism enzymes and performs the redistribution of lipid classes and a decrease in mono-, di-, triglycerides and free fatty acids in the rat liver [8]. Administration of ethylthio sulfanylate induces the increase of total protein and albumin content in rat blood plasma [12]. Also, ethylthiosulfanylate is an effective agent against fungal infections and has antimicrobial effect [9].…”
mentioning
confidence: 99%
“…Тіосульфонатні біоциди ще не були апробовані в легкій промисловості, і нами вперше було вирішено експериментально дослідити антимікробні властивості даних препаратів для текстилю. Це продиктовано не тільки широким спектром дії тіосульфонатних сполук, але й спробою вирішити проблему пошуку малотоксичних та екологічних біоцидів [25,26]. Дані препарати, на нашу думку, можуть ідеально підходити під термінологію «екологічні біоциди», оскільки вони є також діючою субстанцією для лікування різних мікозів шкіри й оніхомікозу нігтів, конкурентоздатного з нізоралом і клотрімазолом.…”
Section: вступunclassified
“…Therefore, ETS affects the metabolism of nucleic acids, which contain amino groups, as well as proteins and amino acids with disulfide and sulfide groups [22]. Thiosulfonates also have a positive influence on metabolic processes in different tissues of rat organisms [23,24]. Furthermore, a thiosulfonate derivative of benzimidazole was tested for its effectiveness as an anticancer agent and showed significant growth inhibition against human tumor cell lines derived from several neoplastic diseases, e.g., leukemia, breast or prostate cancer [25].…”
Section: Introductionmentioning
confidence: 99%